Preparation method and application of platinum-based catalyst taking tin oxide hollow nanofiber as carrier
By using the method of using a tin oxide nano -fiber carrier to embed the PT nanoparticles in the use of a tin oxide nano -fiber carrier, solve the problem of the carbon carrier corrosion and the unstable catalyst, and realize the catalyst of high activity, stability and antisidification performance. It is suitable for High -temperature fuel cell.
Patent Information
- Application Number
- CN202411485353.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
In existing proton exchange membrane fuel cells, carbon support is prone to corrosion, resulting in structural damage and catalytic performance of Pt nanoparticles. The reverse current aggravates carbon oxidation during start-and-stop operation, resulting in unstability of the catalyst.
Tin oxide hollow nanofibers are used as carriers to prepare Pt(5)-SnO2 hollow nanofiber catalysts through electrospinning-reduction-heat treatment methods. The high electrochemical stability and conductivity of SnO2 are used to embed Pt nanoparticles to form high-performance Catalysts with specific surface area and excellent electron mobility.
It significantly improves the activity and stability of the catalyst in the acidic hydrogen oxidation reaction, reduces the poisoning of active sites by CO and phosphoric acid, enhances the anti-poisoning performance of the catalyst, and is suitable for high-temperature proton exchange membrane fuel cells.
Smart Images

Figure CN119361734A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membrane fuel cells, and in particular to a preparation method and application of a platinum-based catalyst using tin oxide hollow nanofibers as a carrier. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) are considered to be one of the most efficient and sustainable electrochemical energy conversion devices. Carbon-supported platinum-based catalysts are universal anode catalysts. Under the working conditions of PEMFC (0.6-0.8V and pH <1), the carbon support of Pt nanoparticles is susceptible to corrosion, resulting in the generation of CO and structural damage. In addition, during the start-stop operation of PEMFC, the local potential of the cathode will reach 1.5V due to the presence of reverse current, which greatly aggravates the further oxidation of the carbon support. Previous studies have shown that the carbon weight loss due to corrosion is about 19% after 4000min of constant potential testing at a potential of 1.5V. After carbon corrosion, the Pt nanoparticles on the surface of the carbon support tend to dissolve and migrate, resulting in a decrease in catalytic performance. At the same time, the weak interaction between Pt and the carbon support makes Pt particles also easy to migrate and aggregate. Considering this, it is urgent to find electrochemically stable and conductive support materials with stronger interactions with Pt nanoparticles to replace carbon for the development of PEMFC technology.
[0003] Metal oxides, such as TiO 2 , SnO 2 and CeO 2 Tin dioxide (SnO) has been investigated as an alternative electrocatalyst support due to its high electrochemical stability and tunable metal-support interactions. 2 ) is a catalyst with abundant reserves, environmental friendliness, stable chemical properties, and large-scale mesopores, which is conducive to faster charge transfer. It is considered to be a promising electrocatalytic support catalyst. SnO 2 It is also a semiconductor metal oxide. Due to its excellent electron mobility and stability, it is an important n-type semiconductor with a wide band gap of 3.6eV. It has been widely used in lithium-ion batteries, photocatalyst oxidation, etc. 2 Materials usually exist in the form of low specific surface area, which is not conducive to charge transfer. Therefore, SnO 2 The surface area of SnO was increased by nanostructure method. 2 Stable fixation, and then embedding Pt nanoparticles into SnO 2The surface of the hollow nanofibers not only increases the specific surface area of the material to expose more active sites, but also constructs hollow nanochannels that are conducive to charge transfer. 2 When Pt nanoparticles are loaded on SnO, it can not only promote the dispersion of Pt nanoparticles, but also reasonably and effectively distribute the adsorbed hydrogen on the active sites during the HOR reaction. Considering that Pt has a high chemical affinity for CO and is easily poisoned by CO, SnO 2 As a charge carrier of Pt nanoparticles, it helps to weaken the binding of CO on Pt, and the established Pt-O-Sn interface plays a key role in electron transfer. At the same time, high-temperature proton exchange membrane fuel cells (HT-PEMFCs) use liquid phosphoric acid as the electrolyte, and Pt-based catalysts react with phosphate anions (H 2 PO 4 - ) has a strong adsorption effect, which makes the catalytic sites poisoned, thereby greatly reducing the HOR activity. 2 The carrier can reduce the adsorption free energy of platinum nanoparticles to phosphoric acid, thereby reducing phosphoric acid poisoning. Moreover, in high-temperature operating systems, SnO 2 The high stability of the carrier can prevent the separation of metal nanoparticles, thus not only avoiding fuel cell poisoning but also maintaining its stability. In-depth research in this area will have a potential breakthrough in improving the mass activity and cycle stability of HOR catalysts, and it is also a strategy worth exploring to improve the power density of high-temperature proton exchange membrane fuel cell anode materials. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and propose a preparation method and application of a platinum-based catalyst using tin oxide hollow nanofibers as a carrier, which makes full use of the stability of the structure and the SnO 2 The excellent electronic conductivity of Pt nanoparticles can fully exert the rational adsorption and desorption of active sites and reaction intermediates, and resist the poisoning of CO and phosphoric acid on active sites. (5) -SnO 2 Hollow nanofibers exhibit excellent activity and stability as acidic hydrogen oxidation electrocatalyst materials.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier comprises the following steps:
[0007] Step S1: Preparation of SnCl 2 / C nanofiber materials
[0008] SnCl 2 ) and polyvinylpyrrolidone (PVP) were added to a mixed solvent of N,N-dimethylformamide (DMF) and ethanol, respectively, and stirred at room temperature for 12 hours. The solution was then transferred to a syringe. The spun fibers were collected using an electrospinning machine and aluminum foil as a collector. SnCl 2 / C nanofiber materials;
[0009] Step S2: Preparation of SnO 2 Hollow Nanofibers
[0010] SnCl 2 The / C nanofiber material was pre-oxidized in a muffle furnace and then oxidized at high temperature to obtain SnO 2 Hollow nanofibers;
[0011] Step S3, preparation of Pt (5) -SnO 2 Hollow Nanofibers
[0012] SnO 2 Hollow nanofibers and potassium chloroplatinate (K 2 PtCl 4 ) was dissolved in deionized water and stirred, and sodium borohydride (NaBH 4 ) aqueous solution, and then centrifugally dried to obtain Pt / SnO 2 , and then heat treated in an inert atmosphere to obtain Pt (5) -SnO 2 Hollow nanofibers.
[0013] Preferably, in step S1, the SnCl 2 The mass ratio of DMF to PVP is 1:2, and the volume ratio of DMF to ethanol is 1:1.
[0014] Preferably, in step S1, the electrospinning machine uses aluminum foil as a collector to collect the spun fibers, and the parameter setting is: the flow rate is 0.04-0.12 mm min -1 , the applied voltage is 10 to 25 kV, and the distance from the nozzle tip to the receiving plate is 8 to 20 cm.
[0015] Preferably, in step S2, the pre-oxidation is carried out by heating the temperature to 100-300°C at a heating rate of 1-4°C / min and keeping the temperature for 1-4h; the high-temperature oxidation is carried out by heating the temperature to 400-600°C at a heating rate of 3-8°C / min and keeping the temperature for 2-4h.
[0016] Preferably, in step S3, the K 2 PtCl 4 and SnO 2 The mass ratio is 1:20, the NaBH4 NaBH in aqueous solution 4 The mass is 0.1g~1g, the reduction time is 1~12h, the drying temperature is 50~80℃, and the drying time is 8~12h.
[0017] Preferably, in step S3, the heat treatment inert atmosphere is N 2 / NH 3 , heat treatment is carried out by heating the temperature to 300-800°C at a heating rate of 1-10°C / min and keeping the temperature for 1-5h.
[0018] A platinum-based catalyst Pt with tin oxide hollow nanofibers as carrier prepared by the above preparation method (5) -SnO 2 , wherein the platinum-based catalyst Pt (5) -SnO 2 Display SnO 2 The hollow long nanofiber structure composed of nanoparticles has an average inner diameter of 150±20nm and an average outer diameter of 200±50nm. Pt nanoparticles are uniformly embedded on the surface of the nanofibers. The large specific surface area of the hollow nanofibers increases the number of exposed active sites. 2 Good conductivity and the unique structure of hollow nanofibers facilitate charge transfer during the reaction and stabilize Pt nanoparticles so that they do not fall off, thus improving the (5) -SnO 2 The activity and stability of the catalyst in acidic HOR. 2 The surface components have excellent electron mobility, stability, and a large band gap, which can prevent CO from poisoning the Pt active sites during the reaction and reduce the adsorption of phosphoric acid on the Pt sites. This property is beneficial for reducing CO and phosphoric acid poisoning of the catalyst when it is used as anode material for high-temperature proton exchange membrane fuel cells.
[0019] The present invention also provides a platinum-based catalyst Pt prepared by the above-mentioned preparation method with tin oxide hollow nanofibers as carrier. (5) -SnO 2 Application in acidic hydrogen oxidation reaction, specifically, platinum-based catalyst Pt based on tin oxide hollow nanofibers as carrier (5) -SnO 2 The rare earth metal oxides described in the present invention present a long hollow nanofiber structure, and Pt nanoparticles are uniformly embedded in the surface of the nanofibers, wherein SnO 2 The carrier can effectively regulate the electronic structure of Pt nanoparticles, greatly reduce the adsorption of CO and phosphate anions on the active sites, and rationally optimize the HBE in the HOR reaction.
[0020] By adopting the above technical solution: stannous chloride (SnCl 2 ) and polyvinyl pyrrolidone (PVP) were added to N, N-dimethylformamide (DMF) and ethanol solvent and mixed evenly, and SnCl was prepared in advance by electrospinning. 2 / C nanofiber material, pre-oxidized and then oxidized at high temperature to oxidize the carbon nanofiber template to form a long hollow SnO 2 Nanofiber material, the material has a regular and uniform morphology, an average inner diameter of 150±20nm, and an average outer diameter of 200±50nm. Pt nanoparticles are then loaded on the surface of the stable hollow nanofibers. Since the catalyst material has a large specific surface area, the exposure rate of the Pt active sites is increased. In addition, SnO 2 As the carrier of Pt nanoparticles, it weakens the binding of CO and Pt, greatly reducing the poisoning effect of CO on the catalyst. 2 PO 4 -) has a strong adsorption effect, which usually causes a large number of catalytic sites in fuel cells to be poisoned. 2 The carrier can reduce the adsorption free energy of platinum nanoparticles to phosphoric acid, thereby reducing phosphoric acid poisoning. In addition, the unadsorbed phosphoric acid can also increase the ion mobility in the electrolyte, thereby accelerating the charge transfer rate between the electrolyte and the electrode surface and improving the HOR reaction kinetics. 2 The surface components of the support have excellent electron mobility and stability, which can not only promote the dispersion of Pt nanoparticles, but also reasonably and effectively distribute the adsorbed hydrogen on the active sites during the HOR reaction, significantly improving the overall HOR activity and stability of the catalyst.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention adopts a simple electrospinning-reduction-thermal adsorption method to prepare Pt with excellent electrochemical activity, high stability, good resistance to CO poisoning and phosphoric acid tolerance. (5) -SnO 2 Hollow nanofiber electrocatalysts.
[0023] 2. SnO selected by the present invention 2 The carrier is abundant in reserves, environmentally friendly, and chemically stable. At the same time, the surface components have excellent electron mobility, which is conducive to faster charge transfer.
[0024] 3. The platinum-based catalyst Pt with tin oxide hollow nanofibers as carrier (5) -SnO 2 The catalyst has a regular morphology and is also 2The carrier regulates the electronic structure and adsorption binding energy of Pt, optimizes its binding strength with H, and thus promotes the adsorption and desorption of reaction intermediates, ultimately achieving an improvement in the catalytic activity of HOR. (5) -SnO 2 Compared with conventional Pt-based materials, the prepared Pt (5) -SnO 2 Hollow nanofibers have unique structural characteristics and carrier advantages, and are a very promising hydrogen oxidation electrocatalyst material, which is expected to have broad application prospects in the future energy industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM spectrum of the platinum-based catalyst prepared in Example 1 of the present invention;
[0026] Figure 2 TEM spectrum of the platinum-based catalyst prepared in Example 1 of the present invention;
[0027] Figure 3 AC-STEM spectrum of the platinum-based catalyst prepared in Example 1 of the present invention;
[0028] Figure 4 The XRD pattern of the platinum-based catalyst prepared in Example 1 of the present invention;
[0029] Figure 5 The Tafel curve of the platinum-based catalyst prepared in Example 1 of the present invention;
[0030] Figure 6 This is a comparison diagram of LSV curves of materials obtained in Example 1 of the present invention and Comparative Examples 1 and 2;
[0031] Figure 7 A comparison diagram of linear fitting curves of micropolarization regions of materials obtained in Example 1 of the present invention and in Comparative Examples 1 and 2;
[0032] Figure 8 This is a phosphoric acid tolerance test curve of the platinum-based catalyst prepared in Example 1 of the present invention;
[0033] Fig. 9 This is a curve diagram of the CO toxicity resistance test of the platinum-based catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] A method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier comprises the following steps:
[0037] 1) Preparation of SnCl 2 / C nanofiber material: 0.5g stannous chloride (SnCl 2 ) and 1g polyvinylpyrrolidone (PVP) were added to a mixed solvent of 6mL N,N-dimethylformamide (DMF) and 6mL ethanol, stirred at room temperature for 12h, and then the solution was transferred to a 10mL syringe. Using an electrospinning machine, the parameters were set as follows: flow rate was 0.06mm min -1 The applied voltage was 20 kV, the distance from the nozzle tip to the receiving plate was 15 cm, and the aluminum foil was used as a collector to collect the spun fibers. SnCl 2 / C nanofiber materials;
[0038] 2) Preparation of SnO 2 Hollow nanofibers: SnCl 2 The SnO / C nanofiber material was pre-oxidized in a muffle furnace at a heating rate of 2°C / min for 2 h at 150°C, and then oxidized at a high temperature of 5°C / min at 500°C to obtain SnO 2 Hollow nanofibers;
[0039] 3) Preparation of Pt (5) -SnO 2 Hollow nanofibers: 100 mg SnO 2 Hollow nanofibers and 5 mg potassium chloroplatinate (K 2 PtCl 4 ) was dissolved in 50 mL of deionized water and stirred, and 0.5 g of sodium borohydride (NaBH 4 ) aqueous solution for 8 h, and then centrifugally dried to obtain Pt / SnO 2 , put it in a tube furnace and heat it at a rate of 2°C / min under N 2 The Pt(5) -SnO 2 Hollow nanofibers.
[0040] The platinum-based catalyst Pt prepared in Example 1 with tin oxide hollow nanofibers as the carrier was characterized by SEM, TEM, XRD and other methods. (5) -SnO 2 Physical characterization. From SEM ( Figure 1 ), it can be seen that the material is composed of interwoven hollow nanofibers with an average inner diameter of 150±20nm and an average outer diameter of 200±50nm. The TEM spectrum ( Figure 2 ) can also clearly show the structural characteristics of its hollow fiber, the wall thickness is 30±20nm. AC-STEM spectrum ( Figure 3 ) shows that Pt nanoparticles are uniformly embedded and exposed in SnO 2 Surface. Figure 4 From the XRD spectrum, it can be seen that the diffraction peak of the material is similar to that of SnO 2 The standard card is completely consistent with that of JCPDS (41-1445), proving that SnO 2 The successful preparation of the nanostructured carbon has no obvious Pt-related diffraction peaks because the amount of Pt doping is very small, and the (002) crystal plane corresponds to the diffraction peak of graphitized carbon.
[0041] From the Tafel curve ( Figure 5 ) or the linear fitting curve of micropolarization region ( Figure 7 ) can be calculated to obtain a higher exchange current density, indicating that it has a faster reaction kinetics rate.
[0042] The above results all indicate that this material has good application prospects as an acidic hydrogen oxidation electrocatalyst material.
[0043] Embodiment 2:
[0044] In this embodiment, the difference from Embodiment 1 is that in Step 1, SnCl 2 The dosage was changed to 1 g, and the rest was the same as in Example 1.
[0045] Embodiment 3:
[0046] In this embodiment, the difference from Example 1 is that the amount of PVP in step 1 is changed to 250 mg, and the rest is the same as Example 1.
[0047] Embodiment 4:
[0048] In this embodiment, the difference from Example 1 is that the amount of DMF in step 1 is changed to 12 mL, and the rest is the same as Example 1.
[0049] Embodiment 5:
[0050] In this embodiment, the difference from Example 1 is that the amount of ethanol in step 1 is changed to 12 mL, and the rest is the same as Example 1.
[0051] Embodiment 6:
[0052] In this embodiment, the difference from embodiment 1 is that the flow rate in step 1 is changed to 0.08 mm min -1 , the rest is the same as Example 1.
[0053] Embodiment 7:
[0054] In this embodiment, different from Embodiment 1, the applied voltage in Step 1 is changed to 18 kV, and the rest is the same as Embodiment 1.
[0055] Embodiment 8:
[0056] In this embodiment, the difference from Embodiment 1 is that the distance from the nozzle tip to the receiving plate in Step 1 is changed to 10 cm, and the rest is the same as Embodiment 1.
[0057] Embodiment 9:
[0058] In this embodiment, different from Embodiment 1, the heating rate of pre-oxidation in Step 2 is changed to 3° C. / min, and the rest is the same as Embodiment 1.
[0059] Embodiment 10:
[0060] In this embodiment, the difference from Embodiment 1 is that the pre-oxidation temperature in Step 2 is changed to 200° C., and the rest is the same as in Embodiment 1.
[0061] Embodiment 11:
[0062] In this embodiment, different from Embodiment 1, the pre-oxidation time in Step 2 is changed to 3 hours, and the rest is the same as Embodiment 1.
[0063] Embodiment 12:
[0064] In this embodiment, the difference from embodiment 1 is that in step 2, SnO 2 The dosage was changed to 200 mg, and the rest was the same as in Example 1.
[0065] Embodiment 13:
[0066] In this embodiment, different from Embodiment 1, K in Step 2 2 PtCl 4 The dosage was changed to 10 mg, and the rest was the same as in Example 1.
[0067] Embodiment 14:
[0068] In this embodiment, unlike in Example 1, NaBH4 The dosage was changed to 0.2 g, and the rest was the same as in Example 1.
[0069] Embodiment 15:
[0070] In this embodiment, unlike in Example 1, NaBH 4 The reduction time was changed to 2 h, and the rest was the same as in Example 1.
[0071] Embodiment 16:
[0072] In this embodiment, different from Embodiment 1, the heating rate of the heat treatment in Step 2 is changed to 5°C / min, and the rest is the same as Embodiment 1.
[0073] Embodiment 17:
[0074] In this embodiment, the difference from Embodiment 1 is that the heat treatment speed in Step 2 is changed to 600° C., and the rest is the same as Embodiment 1.
[0075] Embodiment 18:
[0076] In this embodiment, different from Embodiment 1, the duration of heat treatment in step 2 is changed to 4 hours, and the rest is the same as Embodiment 1.
[0077] Comparative Example 1:
[0078] The only difference from Example 1 is the addition of K 2 PtCl 4 The dosage is 10 mg, and the other implementation conditions remain unchanged.
[0079] Comparative Example 2:
[0080] The only difference from Example 1 is that K is not added 2 PtCl 4 , the other implementation conditions remain unchanged.
[0081] The materials of Example 1 and Comparative Examples 1-2 were subjected to hydrogen oxidation reaction test. Electrochemical measurements were performed using a CHI 660E workstation in 0.1 M HClO 4 The three-electrode system was used in the solution, with a graphite rod and a mercury / calomel electrode as the counter electrode and reference electrode, respectively. 5 mg of catalyst was mixed with 100 uL Nafion (5 wt.%), and then 600 uL deionized water and 300 u ethanol were added to prepare the catalyst ink. After ultrasonic treatment for 30 min, 10 μL of the catalyst ink was evenly dropped on an area of 0.196 cm 2 The glassy carbon electrode was dried at room temperature and used as the working electrode. 2 In saturated electrolyte, the scan rate was 5 mV s -1, the scanning rate is 0.02~1.02V or 0.1~0.5V (vs.RHE), the scanning rate is 1600rpm, and the LSV curve is obtained on RDE. The LSV test results are as follows Figure 6 As shown, Pt (5) -SnO 2 It shows its superior current density, compared with Pt (10) -SnO 2 Performance and Pt (5) -SnO 2 The comparison is slightly worse, pure SnO 2 There is basically no activity. In 0.1M HClO 4 0.01M, 0.05M and 0.1M H were added to the electrolyte respectively. 3 PO 4 , and tested its phosphoric acid tolerance by LSV. It can be clearly concluded that as the phosphoric acid concentration increases, the current density also increases, indicating that Pt (5) -SnO 2 The Pt active sites in the electrolyte are not poisoned by phosphoric acid. Due to the presence of phosphate ions, the ion concentration in the electrolyte increases, which increases the charge flow and the reaction rate. 4 Before the test, pure N was introduced into the electrolyte. 2 The air in the electrolyte was removed. Then, the electrode was kept at 0.1 V vs. RHE for 15 min under bubbling CO gas, and then N 2 The electrolyte was purged for 30 min to completely remove CO in the solution, leaving only a layer of CO on the surface of the working electrode. -1 Under the condition of 0.05V to 1.1V (vs.RHE), the stripping voltammetry of CO was recorded to obtain the anti-CO toxicity test curve. The test results are as follows: Fig. 9 As shown, Pt (5) -SnO 2 The CO dissolution peak starting potential is low and obvious, indicating that the CO adsorbed on the catalyst surface is easily oxidized and desorbed, further enhancing the catalyst's CO tolerance, thus showing that Pt (5) -SnO 2 The advantage of anti-CO poisoning.
[0082] In summary, the present invention loads platinum nanoparticles on a tin oxide hollow nanofiber carrier, utilizes the high activity of platinum nanoparticles and the corrosion resistance and efficient charge transfer of tin oxide to coordinate and optimize the adsorption of acidic hydrogen oxidation (HOR) reaction intermediates, and improves the material's resistance to CO poisoning and phosphoric acid poisoning, ultimately achieving an improvement in the acidic HOR catalytic activity.
[0083] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier, characterized in that: The steps include: Step S1: Preparation of SnCl2 / C nanofiber material Stannous chloride (SnCl2) and polyvinyl pyrrolidone (PVP) were added to a mixed solvent of N,N-dimethylformamide (DMF) and ethanol, respectively, and stirred at room temperature for 12 hours, and then the solution was transferred to a syringe; an electrospinning machine was used, and aluminum foil was used as a collector to collect the spun fibers, and the SnCl2 / C nanofiber material was collected; Step S2: Preparation of SnO2 hollow nanofibers The SnCl2 / C nanofiber material is placed in a muffle furnace for pre-oxidation and then oxidized at high temperature to obtain SnO2 hollow nanofibers. Step S3, preparation of Pt (5) -SnO2 hollow nanofibers SnO2 hollow nanofibers and potassium chloroplatinite (K2PtCl4) were dissolved in deionized water and stirred, and sodium borohydride (NaBH4) aqueous solution was added for reduction, and then centrifuged and dried to obtain Pt / SnO2, which was then heat treated in an inert atmosphere to obtain Pt (5) -SnO2 hollow nanofibers.
2. The method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier according to claim 1, characterized in that: In step S1, the mass ratio of SnCl2 to PVP is 1:2, and the volume ratio of DMF to ethanol is 1:
1.
3. The method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier according to claim 1, characterized in that: In step S1, the electrospinning machine uses aluminum foil as a collector to collect the spun fibers, and the parameter setting is: the flow rate is 0.04-0.12 mm min -1 , the applied voltage is 10 to 25 kV, and the distance from the nozzle tip to the receiving plate is 8 to 20 cm.
4. The method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier according to claim 1, characterized in that: In step S2, the pre-oxidation is to heat up to 100-300°C at a heating rate of 1-4°C / min and keep warm for 1-4h; the high-temperature oxidation is to heat up to 400-600°C at a heating rate of 3-8°C / min and keep warm for 2-4h.
5. The method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier according to claim 1, characterized in that: In step S3, the mass ratio of K2PtCl4 to SnO2 is 1:20, the mass of NaBH4 in the NaBH4 aqueous solution is 0.1g to 1g, the reduction time is 1 to 12h, the drying temperature is 50 to 80°C, and the drying time is 8 to 12h.
6. The method for preparing a platinum-based catalyst using tin oxide hollow nanofibers as a carrier according to claim 1, characterized in that: In step S3, the heat treatment inert atmosphere is N2 / NH3, and the heat treatment is heated to 300-800°C at a heating rate of 1-10°C / min and kept at that temperature for 1-5h.
7. A platinum-based catalyst Pt prepared by the preparation method according to any one of claims 1 to 6 with tin oxide hollow nanofibers as carrier (5) -SnO2.
8. A platinum-based catalyst Pt prepared by the preparation method according to any one of claims 1 to 6 with tin oxide hollow nanofibers as carrier (5) -Application of SnO2 in acidic hydrogen oxidation reaction.
Citation Information
Patent Citations
Platinum-loaded tin dioxide nanofiber gas-sensitive material and gas-sensitive element made from same
CN105628748A
Platinum-based nanoparticle coating and tin dioxide covering carbon nanotube and preparation method thereof
CN106784900A
Hollow porous carbon nanofiber with tin oxide loaded on inner tube wall as well as preparation method and application of hollow porous carbon nanofiber
CN113564752A
Fibrous SnO nano powder and preparation method thereof
CN113860359A
Low-platinum-based catalyst Pt-N-C as well as preparation method and application thereof
CN117438603A